Soil fungal taxonomic and functional community composition as affected by biochar properties. (November 2018) - Dai, Zhongmin; Enders, Akio; Rodrigues, Jorge L.M.; Hanley, Kelly L.; Brookes, Philip C.; Xu, Jianming; Lehmann, Johannes
Abstract: Biochar greatly influences the soil bacterial community and nutrient transformations, while our knowledge of the responses of fungal lifestyles to biochar is still in its infancy. Here, we used experimental pre-treatments (acetone extraction) of nutrient-rich biochars to identify which major biochar properties influence fungi the most: the easily mineralizable C, fused aromatic backbone, or the inorganic nutrients of biochars. Our objective was to investigate how different biochar fractions (easily mineralizable C, fused aromatic C, nutrients) structure the fungal taxonomic and functional communities. The easily mineralizable C of biochars induced greater short-term changes in fungal community composition compared to the fused aromatic C. The easily mineralizable C significantly decreased the relative abundance of Basidiomycota by avg. 10.6%, while it had no effects on Ascomycota and Zygomycota . Co-occurrence network indicated that saprophytic fungi were self-assembled in the easily mineralizable C-sufficient environment, whereas they were the connectors to interact with other groups when lower amounts of energy in form of mineralizable C were present. Thus, the easily mineralizable C in biochar as a microbial C source probably promoted saprotroph growth, caused them to self-assemble and to enhance their competitive capacity, leading to overall diversity decrease and relative decline of fungal pathogens. The inorganic nutrients had no effects on fungal diversity and saprotroph abundance, while they decreased the relative abundance of Zygomycota . Our study highlighted the important roles of both mineralizable C and inorganic nutrients in modification of the fungal community, and demonstrated that biochar probably favors the growth of saprotrophs over soil-borne fungal pathogens. Highlights: Biochar changed fungal taxonomic and functional community composition. Isolation of biochar properties points to fungal response to C vs structure or nutrients. Easily mineralizable C in biochars decreased the relative abundance of Basidiomycota. Easily mineralizable C promoted saprotroph growth and decreased fungal diversity.